New species, Coelogyne sondangii (Orchidaceae), and a new national record, C. moi, in Vietnam - Vo, Doan Trung; Averyanov, Leonid V.; Maisak, Tatiana V.; Bui, van Huong; Nguyen, van Canh; Dang, Minh Quan; Nguyen, Quoc Bao; Truong, Ba Vuong (Phytotaxa, 2022)
Coelogyne sondangii is described as a species new for science. It allies to the group of former Panisea species with white flowers, namely C. albiflora, C. demissa, C. yunnanensis, C. panchaseensis, and C. sagittata, but differs from them in big flowers, narrowly spatulate lip with erose margin of lobes and irregularly denticulate column wings. In addition, C. moi is firstly recorded and documented for the flora of Vietnam, as well as new nomenclatural combination, Coelogyne sagittata (T.C.Hsu, H.C.Hung & Luu) Vuong & Aver., is proposed.